Prevalence of Helicobacter pylori infection in the general population in Wuzhou, China: a cross-sectional study - Liumei Yan; Qiliang He; Xinyun Peng; Sen Lin; Meigu Sha; Shujian Zhao; Dewang Huang; Jiemei Ye (Infectious Agents and Cancer)
Abstract Background Helicobacter pylori (H. pylori) is a global infectious carcinogen. We aimed to evaluate the prevalence of H. pylori infection in the healthcare-utilizing population undergoing physical examinations at a tertiary hospital in Guangxi, China. Furthermore, gastroscopies were performed on selected participants to scrutinize the endoscopic features of H. pylori infection among asymptomatic individuals. Subjects and methods This study involved 22,769 participants who underwent H. pylori antibody serology screenings at the hospital between 2020 and 2023. The 14C-urea breath test was employed to determine the current H. pylori infection status of 19,307 individuals. Concurrently, 293 participants underwent gastroscopy to evaluate their endoscopic mucosal abnormalities. The risk correlation and predictive value of endoscopic mucosal traits, Hp infection status, and 14C-urea breath test(14C-UBT) outcomes were investigated in subsequent analyses. Results Serum Ure, CagA, and VacA antibodies were detected in 43.3%, 27.4%, and 23.6% of the 22,769 subjects that were screened, respectively. The population exhibited 27.5% and 17.2% positive rates for immune type I and II, respectively. Male participants exhibited lower positive rates of serum antibodies than females. The positive rates and predictive risks of the antibodies increased with age, and the highest positive rates were observed in the 50–60 age subgroup. Based on the outcomes of serological diagnostic techniques, it was observed that the positive rate was significantly higher compared to that of non-serological diagnostic methods, specifically the 14C-UBT results (43.3% versus 14.97%). Among the other cohort (n = 19,307), the 14C-UBT revealed a 14.97% positivity rate correlated with age. The 293 individuals who underwent gastroscopy from 14C-UBT Cohort were found to be at an increased risk of a positive breath test if they exhibited duodenal bulb inflammation, diffuse redness, or mucosal edema during the gastroscopy visit. Conclusion The prevalence of Helicobacter pylori infection is high among the population of Wuzhou, Guangxi, China. Type I H. pylori strains, distinguished by their enhanced virulence, are predominant in this region. In the framework of this population-based study, age has been identified as an independent risk factor for H. pylori infection. Additionally, distinct mucosal manifestations observed during gastroscopy can facilitate the identification of healthcare-utilizing individuals with active H. pylori infections.